A silicate adhesive and a method for preparing the same

CN122898217APending Publication Date: 2026-10-13LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202611289511.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0007]专利公布号为CN103059748A公布的一种改性硅酸盐无机胶粘剂,虽然具有良好的粘结力,但是溶剂中丙酮,甲苯二异氰酸酯和N,N-二甲基甲酰胺的添加使其环保性降低,限制了应用

Benefits of technology

1)本发明提供的所述硅酸盐胶粘剂可持续在1600℃高温环境中使用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898217A_ABST
    Figure CN122898217A_ABST
Patent Text Reader

Abstract

The application provides a silicate adhesive and a preparation method thereof, and belongs to the technical field of inorganic adhesives.The adhesive comprises the following components in parts by weight: 26-30 parts of silicate resin, 1.7-2.2 parts of a curing agent, 20-25 parts of a metal oxide, 0.25-0.55 parts of metal powder, 0.15-0.36 parts of modified glass powder, 0.23-0.27 parts of modified zirconia fiber, 0.13-0.17 parts of a surfactant, 0.28-0.32 parts of a dispersing agent, 0.29-0.33 parts of a defoaming agent, and the rest is solvent.The adhesive has excellent high-temperature resistance, high-low temperature alternating cycle performance, acid and alkali resistance, and low water absorption.The adhesive is environment-friendly and non-toxic, and belongs to an environment-friendly material, and is a candidate material for mechanical parts in extreme working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of inorganic adhesives, specifically to a silicate adhesive and its preparation method. Background Technology

[0002] Inorganic adhesives are a class of adhesives made primarily from natural silicon, calcium compounds, and other similar raw materials, mainly including alkali metal silicates and phosphates. The preparation of inorganic adhesives often involves high-temperature reactions, resulting in high bonding strength, high-temperature resistance, low cost, simple structure, and good flame retardancy. They are widely used for bonding materials, especially in high-temperature environments, achieving material conservation, energy saving, and simplified processes. However, aerospace (hypersonic vehicles and their missiles, satellites, and rockets), weaponry, and nuclear energy (nuclear reactor core instruments) fields have placed higher demands on adhesives operating under harsh conditions for extended periods, addressing common challenges such as high-temperature resistance, resistance to thermal cycling, and bonding performance. Therefore, developing new inorganic adhesives that meet operational requirements and offer superior overall performance is urgently needed.

[0003] Silicate adhesives are an important branch of inorganic adhesives. They are high-temperature resistant, chemically reactive inorganic adhesives formulated from alkali metal silicates, curing agents, fillers, additives, and diluents. Silicate adhesives can be used in a wide temperature range of -196℃ to 1600℃ and possess excellent bonding properties, temperature resistance, solvent resistance, chemical resistance, environmental friendliness, and low cost.

[0004] The silicate inorganic adhesive disclosed in patent publications CN106519993A and CN113683966A improves the surface gloss and density of silicate inorganic adhesive by adding glycerol and methylcellulose. However, its shear strength of steel-to-steel overlap is only 3.2~3.7MPa, and its sleeve strength of steel-to-steel sleeve is only 22.0~25.5MPa.

[0005] In the impact-resistant seawall repair adhesive and its preparation method disclosed in CN117327452A, the bonding strength of the silicate adhesive for ceramic sheets in air, seawater and tap water media is only 1.0~1.4MPa, 0.65~0.76MPa and 0.63~0.94MPa, respectively.

[0006] The adhesive in the high-temperature resistant inorganic adhesive and its preparation method disclosed in patent publication number CN115353809A has a bonding strength of only 23.8~25.2MPa for steel-fireproof board and only 15.4~16.2MPa for ceramic-ceramic, which is far below the service requirements of modern thermal protection adhesive materials.

[0007] A modified silicate inorganic adhesive disclosed in patent publication number CN103059748A has good adhesion, but the addition of acetone, toluene diisocyanate and N,N-dimethylformamide in the solvent reduces its environmental friendliness and limits its application.

[0008] It is evident that existing silicate adhesives suffer from drawbacks such as low bonding strength between the adhesive and the substrate, failing to meet the service requirements of modern thermal protective adhesives, short duration of continuous high-temperature resistance, low number of thermal cycling cycles, high brittleness, and the need for the addition of organic solvents. Therefore, designing and preparing silicate adhesives that can withstand harsh operating conditions, are environmentally friendly, and cost-effective is of great significance. Summary of the Invention

[0009] In view of this, the present invention provides a silicate adhesive comprising, by weight, the following components: The composition includes 26-30 parts silicate resin, 1.7-2.2 parts curing agent, 20-25 parts metal oxide, 0.25-0.55 parts metal powder, 0.15-0.36 parts modified glass powder, 0.23-0.27 parts modified zirconia fiber, 0.28-0.32 parts dispersant, 0.29-0.33 parts defoamer, and the balance being solvent.

[0010] Furthermore, the preparation method of the modified glass powder includes the following steps: γ-glycidoxypropyltrimethoxysilane and vinyltriethoxysilane were mixed in a certain proportion and then added to a certain amount of anhydrous ethanol. The mixture was stirred until homogeneous to obtain a mixed liquid with a mass fraction of 1.0-5.5%. Glass powder was added to the mixed liquid and the reaction was carried out. After the reaction was completed, the mixture was filtered and dried to obtain modified glass powder.

[0011] Furthermore, the mass ratio of γ-glycidoxypropyltrimethoxysilane to vinyltriethoxysilane is 1:3-5; the amount of the mixture of γ-glycidoxypropyltrimethoxysilane and vinyltriethoxysilane added accounts for 1.2%-3.7% of the total mass of the glass powder; the D of the glass powder... 50 The size is 180-300 μm; the reaction temperature is 50-80℃, and the reaction time is 30-180 min.

[0012] Furthermore, the preparation method of the modified zirconia fiber includes the following steps: (1) Immerse the zirconium oxide fiber in a dopamine hydrochloride solution and sonicate for 20-50 min. Adjust the pH of the system to the range of 7.5-8.5. Stir and react at room temperature. After the reaction is completed, wash with water and dry to obtain the preliminary modified fiber. (2) The preliminarily modified fiber is immersed in an ethanol dispersion of europium nitrate at 2.5-4.0 g / L, stirred at 55°C for 1-3 h, and then centrifuged, washed with water and dried to obtain modified zirconia fiber.

[0013] Furthermore, in step (1), the zirconium oxide fiber has a diameter of 1~6μm and a length of less than 5mm; the concentration of the hydrochloric acid dopamine solution is 0.02 mol / L-0.05 mol / L; the pH value of the system is adjusted using Tris buffer solution with a concentration of 0.01 mol / L; the reaction time is 1-3 h; the drying temperature is 60-80℃; during soaking in steps (1)-(2), ensure that the fiber is completely submerged at least 1-2 cm below the liquid surface to ensure that the fiber bundle is fully wetted.

[0014] Furthermore, the silicate resin is any one or two of sodium silicate resin and potassium silicate resin; the sodium silicate resin has a modulus of 3.1 to 3.3, a silicon dioxide (SiO2) content of 25%, and a solid content of 65%; the potassium silicate resin has a modulus of 2.3 to 2.5, a silicon dioxide (SiO2) content of 20%, and a solid content of 61%.

[0015] Furthermore, the curing agent is any one of fluorosilicate, metaborate, tripolyphosphate, and chloropalmitoyl methyl ester, and the curing agent is white with a purity ≥99%.

[0016] Furthermore, the metal oxide is any one of silicon dioxide, zirconium dioxide, aluminum oxide, cobalt oxide, iron oxide, and chromium oxide, with a purity ≥99% and a particle size ≤5μm.

[0017] Furthermore, the metal powder is any one of Cu powder, Al powder, and Fe powder, with a purity ≥99% and a particle size ≤5μm.

[0018] Furthermore, the surfactant is a polyether-modified siloxane; the dispersant is a styrene-maleic anhydride copolymer; the defoamer is a mixture of a high-boiling-point solvent and a defoaming substance; and the solvent is a mixed solution of anhydrous ethanol and water.

[0019] The present invention also provides a method for preparing the silicate adhesive, comprising the following steps: (1) Weigh the dispersant and add an appropriate amount of solvent and stir to obtain intermediate A; (2) The weighed modified zirconium oxide fiber was added to intermediate A and stirred to obtain intermediate B; (3) Weigh the surfactant, add an appropriate amount of solvent and stir to obtain intermediate C; (4) Add the weighed metal oxide, metal powder and modified glass powder to intermediate C and stir to obtain intermediate D; (5) Weigh the silicate resin, add an appropriate amount of solvent and stir evenly, then add the curing agent to obtain intermediate E; (6) Slowly add intermediate D to intermediate E and stir until the mixture is evenly distributed to form slurry F; (7) Slowly add intermediate B to slurry F and stir. After mixing evenly, add defoamer to form slurry G; (8) Grind the slurry G in a grinding instrument to obtain silicate adhesive.

[0020] Furthermore, in steps (1) to (7), the stirring time is 30 to 60 minutes; in step (8), the grinding rate is 1 to 3 r / min.

[0021] The present invention also provides a method for using the silicate adhesive, comprising the following steps: applying the silicate adhesive to a substrate, heating and curing, and then cooling it to room temperature in the oven after curing.

[0022] Furthermore, the curing temperature is 160-230℃, and the curing time is (2~3) h.

[0023] Compared with the prior art, the present invention has the following beneficial effects: 1) The silicate adhesive provided by the present invention can be used continuously in a high-temperature environment of 1600°C.

[0024] 2) The silicate adhesive provided by the present invention can achieve a tensile shear strength of 28.1 MPa on the surface of the joint between rigid materials.

[0025] 3) The bonding strength between the silicate adhesive provided by the present invention and the rigid material matrix can reach 58.6 MPa.

[0026] 4) The silicate adhesive provided by the present invention does not bubble or peel off after being repeatedly used 50 times in a high and low temperature alternating cycle from room temperature to 1600℃.

[0027] 5) The silicate adhesive provided by the present invention does not bubble or peel off when soaked in 30% hydrochloric acid or 30% NaOH medium for 24 hours.

[0028] 6) The silicate adhesive provided by the present invention has a bonding strength of grade 1 after soaking in pure water for 24 hours and a water absorption of less than 2%. Attached Figure Description

[0029] The present invention will be further described below with reference to the accompanying drawings.

[0030] Figure 1 This is a schematic diagram showing the connection between the silicate adhesive and the substrate described in this invention.

[0031] Figure 2 This is a schematic diagram of the tensile shear strength test of the silicate adhesive described in this invention. Detailed Implementation

[0032] This invention provides a silicate adhesive, comprising the following components in parts by weight: The composition includes 26-30 parts silicate resin, 1.7-2.2 parts curing agent, 20-25 parts metal oxide, 0.25-0.55 parts metal powder, 0.15-0.36 parts modified glass powder, 0.23-0.27 parts modified zirconia fiber, 0.13-0.17 parts surfactant, 0.28-0.32 parts dispersant, 0.29-0.33 parts defoamer, and the balance being solvent.

[0033] In some embodiments of the present invention, the method for preparing the modified glass powder includes the following steps: γ-glycidoxypropyltrimethoxysilane and vinyltriethoxysilane were mixed in a certain proportion and then added to a certain amount of anhydrous ethanol. The mixture was stirred until homogeneous to obtain a mixed liquid with a mass fraction of 1.0-5.5%. Glass powder was added to the mixed liquid and the reaction was carried out. After the reaction was completed, the mixture was filtered and dried to obtain modified glass powder.

[0034] In some embodiments of the present invention, the mass ratio of γ-glycidoxypropyltrimethoxysilane to vinyltriethoxysilane is 1:3-5; the amount of the mixture of γ-glycidoxypropyltrimethoxysilane and vinyltriethoxysilane added accounts for 1.2%-3.7% of the total mass of the glass powder; the D of the glass powder... 50 The size is 180-300 μm; the reaction temperature is 50-80℃, and the reaction time is 30-180 min.

[0035] During their research, the inventors discovered that adding glass powder to the silicate adhesive system resulted in an excessively large difference in the coefficients of thermal expansion between the adhesive and the ceramic matrix. This caused excessive thermal stress during use at high temperatures, damaging the interfacial adhesion and making the interface prone to cracking or peeling. Furthermore, during long-term service, temperature changes led to repeated stress, causing micro-cracks between the adhesive and the ceramic matrix. This posed a risk of cracking or even complete breakage of the ceramic matrix, shortening its lifespan.

[0036] Furthermore, the adhesive strength of the adhesive decreased significantly after the addition of glass powder. This may be because silicate resin cures to form a glass-ceramic phase, and adding glass powder to the silicate adhesive disrupts this glass phase, leading to reduced adhesive strength. Additionally, the poor compatibility of glass powder with other components affects the adhesive's density, further reducing its adhesive strength.

[0037] To overcome the aforementioned problems, this invention employs a composite organosilicon modifier to modify glass powder. Specifically, the vinyl and ethoxysilane groups on vinyltriethoxysilane can undergo a grafting reaction with the silanol groups on the glass powder surface. The grafted glass powder is chemically bonded into the cured cross-linked network, significantly improving the adhesive strength. Simultaneously, the modified glass powder and metal oxide synergistically adjust the coefficient of thermal expansion, ensuring that the adhesive's coefficient of thermal expansion is essentially consistent with that of the ceramic matrix. This prevents excessive thermal stress from damaging the bond during high-temperature use, improving the temperature resistance and adhesive strength of the silicate adhesive. Furthermore, modification with the composite organosilicon modifier changes the surface of the glass powder from hydrophilic to hydrophobic, thereby improving the interfacial compatibility between the glass powder and the silicate resin matrix, reducing interfacial defects, and enhancing adhesive strength.

[0038] During the curing process of silicate adhesives, the glycidyl ether oxygen functional groups on the γ-glycidyl etheroxypropyltrimethoxysilane can chemically react with the hydroxyl groups on the surface of the silicate resin, effectively preventing brittle cracking of the silicate adhesive in alternating hot and cold environments or severe vibration environments, improving the temperature resistance of the adhesive, and extending its service life. Furthermore, modification with a composite organosilicon modifier can improve the dispersibility of glass powder, enhancing the density and mechanical strength after curing.

[0039] In addition, the modified glass powder can form hydrogen bonds and ionic bonds with silicate resin, further improving the bonding strength, and the two produce a synergistic effect.

[0040] In some embodiments of the present invention, the method for preparing the modified zirconia fiber includes the following steps: (1) Immerse the zirconium oxide fiber in a dopamine hydrochloride solution and sonicate for 20-50 min. Adjust the pH of the system to the range of 7.5-8.5. Stir and react at room temperature. After the reaction is completed, wash with water and dry to obtain the preliminary modified fiber. (2) The preliminarily modified fiber is immersed in an ethanol dispersion of europium nitrate at 2.5-4.0 g / L, stirred at 55°C for 1-3 h, and then centrifuged, washed with water and dried to obtain modified zirconia fiber.

[0041] In some embodiments of the present invention, the zirconium oxide fiber in step (1) has a diameter of 1~6μm and a length of less than 5mm; the concentration of the hydrochloric acid dopamine solution is 0.02 mol / L-0.05 mol / L; the pH value of the system is adjusted by using Tris buffer solution with a concentration of 0.01 mol / L; the reaction time is 1-3 h; the drying temperature is 60-80℃; during soaking in steps (1)-(2), ensure that the fiber is completely submerged at least 1-2 cm below the liquid surface to ensure that the fiber bundle is fully wetted.

[0042] Traditional adhesive preparation processes typically involve adding inorganic fibers, such as zirconia fibers, to improve the crack resistance of adhesives. However, practical research has revealed that the chemical inertness of the zirconia fiber surface leads to unsatisfactory interfacial bonding strength in silicate adhesive systems, making it prone to unstable microcracks during long-term use, especially in high-temperature environments or environments with frequent temperature changes. To address this issue, this invention first uses polydopamine to preliminarily modify zirconia fibers. Polydopamine modification enhances the free energy and roughness of the zirconia fiber surface, thereby promoting penetration between the zirconia fiber and the matrix, improving interfacial bonding strength, and exhibiting better crack resistance. Polydopamine can also chelate metal ions, reducing metal ion shedding. Next, this invention grafts the preliminarily modified fibers, rich in hydroxyl groups, with europium nitrate to obtain modified zirconia fibers, improving the interfacial properties between the zirconia fibers and the matrix, and enhancing shear strength, toughness, high-temperature resistance, and water resistance.

[0043] In some embodiments of the present invention, the silicate resin is any one or both of sodium silicate resin and potassium silicate resin; the sodium silicate resin has a modulus of 3.1 to 3.3, a silicon dioxide (SiO2) content of 25%, and a solid content of 65%, and is a commercially available industrial-grade product; the potassium silicate resin has a modulus of 2.3 to 2.5, a silicon dioxide (SiO2) content of 20%, and a solid content of 61%, and is a commercially available industrial-grade product. Preferably, the silicate resin is compounded from sodium silicate resin and potassium silicate resin in a mass ratio of (1.5 to 2.3):(0.8 to 1.1).

[0044] The curing of the single-component silicate adhesive described in this invention is a physicochemical reaction. The curing of silicates mainly involves the evaporation of moisture and the condensation between active groups within the silicate and between the active groups of the filler, forming a network structure. As the curing temperature increases, the condensation reaction between the active groups intensifies, leading to a tight bond between the filler particles. This results in a strong cohesive strength in the cured adhesive, exhibiting excellent bonding performance. The -Si-O-Si- bonds with high bond energy and polarity formed during curing are the main reason for the oxidation resistance of the silicate adhesive, and also the main reason for ensuring the adhesive's high thermal stability and strong thermal shock resistance.

[0045] The single-component silicate adhesive compound structure described in this invention achieves a significant improvement in physicochemical properties and environmental applicability. The metal ions (Al) selected in this invention from the metal oxide... 3+ Cr 3+ (etc.) and Si 4+ The ionic radii are similar, and by replacing part of the Si 4+Entering the silicon-oxygen tetrahedron, it undergoes multi-anionic polymerization to form a very strong Si-OM (where M is Zr). 4+ Al 3 + Ti 4+ Cr 3+ and Mg 2+ The three-dimensional mesh structure enhances the adhesive's bonding strength. Simultaneously, the added metal powder can also replace some of the Si content. 4+ This forms Si-ON (where N is Al). 3+ Fe 3+ and Cu 2+ This bond further enhances the cohesive strength of the adhesive.

[0046] On the other hand, the addition of metal powder can shield the matrix material from corrosion and improve the toughness of the adhesive. It also improves the interface and hinders the propagation of microstructure cracks.

[0047] The doped modified zirconia fibers are interwoven throughout the three-dimensional structure, forming a three-dimensional interlaced skeleton structure that endows the single-component silicate adhesive with rigidity and elasto-plasticity. This adjusts the adhesive's coefficient of thermal expansion to match the substrate, reducing the risk of adhesive cracking. The addition of these fillers significantly improves the strength, water resistance, and thermal shock resistance of the silicate adhesive.

[0048] In some embodiments of the present invention, the curing agent is any one of fluorosilicate, metaborate, tripolyphosphate, and chloropalmitoyl methyl ester, and the curing agent is white with a purity ≥99%.

[0049] Preferably, the fluorosilicate is either magnesium fluorosilicate or sodium fluorosilicate; the metaborate is either magnesium metaborate or sodium metaborate; and the tripolyphosphate is either sodium tripolyphosphate or aluminum tripolyphosphate. More preferably, the curing agent is methyl palmitate.

[0050] In some embodiments of the present invention, the metal oxide is any one of silicon dioxide, zirconium dioxide, aluminum oxide, cobalt oxide, iron oxide and chromium oxide, with a purity ≥99% and a particle size ≤5μm.

[0051] In some embodiments of the present invention, the metal powder is any one of Cu powder, Al powder and Fe powder, with a purity ≥99% and a particle size ≤5μm.

[0052] In some embodiments of the present invention, the surfactant is a polyether-modified siloxane; preferably, the polyether-modified siloxane is any one of TEGOPREN 5840, BYK-310, BYK-349, BYK-3456, BYK-3760, BYK-333 and BYK-348.

[0053] In some embodiments of the present invention, the dispersant is a styrene-maleic anhydride copolymer; preferably, the styrene-maleic anhydride copolymer is either DISPERBYK-2013 or DISPERBYK-190.

[0054] In some embodiments of the present invention, the defoamer is a mixture of a high-boiling-point solvent and a defoaming substance; preferably, the mixture of the high-boiling-point solvent and the defoaming substance is BYKETOL-WA.

[0055] In some embodiments of the present invention, the solvent is a mixed solution of anhydrous ethanol and water; preferably, the solvent is a mixed solution of anhydrous ethanol and water in a volume ratio of (25~35):(65~85).

[0056] The functions of each component are explained below: In aqueous solutions of silicate resin adhesives, free SiO2 molecules polymerize to form an unstable polymer, nSiO2. During heat curing, the polymer undergoes dehydration condensation reactions, gradually forming a [SiO4] tetrahedral structure linked by -Si-O-Si- bonds. The [SiO4] tetrahedra interact, ultimately forming a three-dimensional network structure that adheres to the surface of the part.

[0057] Curing agents promote the curing reaction of silicate resins, forming cross-linked structures, which significantly improves the physicochemical properties of the materials.

[0058] The addition of metal oxides can improve the temperature resistance and bond strength of silicate adhesives.

[0059] The addition of metal powder not only improves the adhesive strength and thermal stability of the adhesive, but also increases its toughness.

[0060] The addition of modified glass powder adjusts the coefficient of thermal expansion, thereby improving the temperature resistance and bonding strength of silicate adhesives.

[0061] Modified zirconia fibers enhance the flexibility of the adhesive by bridging the skeleton, while also improving interfacial bonding strength, shear strength, toughness, high temperature resistance, and water resistance.

[0062] Surfactants reduce the surface tension of the mixed solvent, thereby increasing its wettability with the substrate.

[0063] The dispersant mainly adheres to the surface of the filler, forming a vacancy barrier effect and improving its uniform distribution.

[0064] Adding defoamer can effectively improve workability.

[0065] The present invention also provides a method for preparing the silicate adhesive, comprising the following steps: (1) Weigh the dispersant and add an appropriate amount of solvent and stir to obtain intermediate A; (2) The weighed modified zirconium oxide fiber was added to intermediate A and stirred to obtain intermediate B; (3) Weigh the surfactant, add an appropriate amount of solvent and stir to obtain intermediate C; (4) Add the weighed metal oxide, metal powder and modified glass powder to intermediate C and stir to obtain intermediate D; (5) Weigh the silicate resin, add an appropriate amount of solvent and stir evenly, then add the curing agent to obtain intermediate E; (6) Slowly add intermediate D to intermediate E and stir until the mixture is evenly distributed to form slurry F; (7) Slowly add intermediate B to slurry F and stir. After mixing evenly, add defoamer to form slurry G; (8) Grind the slurry G in a grinding instrument to obtain silicate adhesive.

[0066] In some embodiments of the present invention, in steps (1) to (7), the stirring time is 30 to 60 min; in step (8), the grinding rate is 1 to 3 r / min.

[0067] The present invention also provides a method for using the silicate adhesive, comprising the following steps: applying the silicate adhesive to a substrate, heating and curing, and then cooling it to room temperature in the oven after curing.

[0068] In some embodiments of the present invention, the curing temperature is 160-230°C, and the curing time is 2-3 hours. Preferably, the curing temperature is 204°C, and the curing time is 2.5 hours.

[0069] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0070] Unless otherwise specified, the test methods or experimental methods described in the following examples are all conventional methods; unless otherwise specified, the raw materials and additives are obtained from conventional commercial sources or prepared by conventional methods.

[0071] Some of the raw materials used in the following examples or comparative examples are as follows: The sodium silicate resin has a modulus of 3.1 to 3.3, a silicon dioxide (SiO2) content of 25%, and a solid content of 65%; the potassium silicate resin has a modulus of 2.3 to 2.5, a silicon dioxide (SiO2) content of 20%, and a solid content of 61%.

[0072] The curing agent (any one of magnesium fluorosilicate, sodium fluorosilicate, magnesium metaborate, sodium metaborate, sodium tripolyphosphate, and aluminum tripolyphosphate) is white and has a purity of ≥99%.

[0073] Metal oxides, purity ≥99%, particle size 5μm.

[0074] Metal powder, purity ≥99%, particle size 5μm.

[0075] D of modified glass powder 50 It is 180-300μm.

[0076] The diameter of the modified zirconia fiber is 1~6μm.

[0077] The testing method is as follows: (1) Viscosity was tested on an NDJ-8S rotational viscometer according to GB / T 2794-2022, using rotor No. 2 and a rotation speed of 6 r / min.

[0078] (2) pH value was tested according to GB / T 9724-2006.

[0079] (3) The bonding strength was tested according to GB / T 5210-2006 using a BGD 500 / S tester with a spindle diameter of 10 mm and a pressurization rate of 0.4 MPa / s.

[0080] (4) Acid and alkali resistance is tested according to GB / T 9274-1988, where the acid medium is 30% hydrochloric acid solution and the alkali medium is 30% NaOH solution.

[0081] (5) Tensile shear strength was tested according to GB / T 7124-2008. The schematic diagram of the specimen is shown below. Figure 2 As shown. Test conditions: The test substrate was 316L stainless steel, the specimen size was 100mm × 25mm × (1.5~2.0)mm, the overlap length was (12.5-0.25)mm, and the bonding area was 312.5mm². 2The adhesive layer thickness is (0.15~0.20) mm, and the loading rate is 5 mm / min. The overlapping surfaces are sanded / blasted, degreased with acetone / ethanol, and dried. The adhesive is applied as soon as possible to ensure that the force is along the shear plane without eccentricity.

[0082] (6) Test the temperature resistance performance according to GB / T 1735-2009. Test conditions: Apply silicate adhesive to the surface of alumina ceramic with dimensions of 120mm×50mm×5mm, and place it in a muffle furnace after complete curing. Keep it at a constant temperature of (1600-10)℃ for 4 hours, and then cool it to room temperature with the furnace. Observe whether there are cracks, peeling, or detachment on the surface of the adhesive.

[0083] (7) The high and low temperature cycling performance of the silicate adhesive prepared according to GB / T 30873-2014 was tested. The silicate adhesive of the present invention was applied to the surface of an alumina ceramic with dimensions of 114mm×64mm×64mm, and the cured sample was placed in a muffle furnace. After being kept at (1600±10)℃ for 15min, it was directly taken out and air-cooled to room temperature as one cycle.

[0084] (8) The water resistance of the silicate adhesive prepared according to GB / T 8810-2005 was tested. The sample substrate was a 316L stainless steel block with dimensions of 25 mm × 25 mm × 2 mm. The water absorption rate was calculated by weighing the sample after it was immersed in water at 23℃ for 24 h.

[0085] Example 1 A silicate adhesive comprising the following components by weight: The composition comprises 27.5 parts sodium silicate resin, 2.1 parts curing agent (sodium fluorosilicate), 21.4 parts metal oxide (zirconia), 0.26 parts metal powder (Cu powder), 0.26 parts modified glass powder, 0.24 parts modified zirconia fiber, 0.13 parts surfactant (BYK-310), 0.28 parts dispersant (DISPERBYK-2013), and 0.3 parts defoamer, with the balance being 47.79 parts solvent. The solvent, by volume percentage, is composed of 25% anhydrous ethanol and 75% deionized water.

[0086] The modified glass powder is prepared as follows: γ-glycidoxypropyltrimethoxysilane and vinyltriethoxysilane were mixed at a mass ratio of 1:4 to obtain a composite organosilicon modifier. The mixture was placed in anhydrous ethanol and stirred until homogeneous to obtain a mixed liquid with a mass fraction of 3.5%. The amount of the composite organosilicon modifier added accounted for 2.0% of the total mass of the glass powder. Glass powder was added to the mixed liquid and reacted at 60°C for 120 min. After the reaction was completed, the mixture was filtered and dried in an oven at 105°C for 3 h to obtain modified glass powder.

[0087] The preparation method of the modified zirconia fiber includes the following steps: (1) Zirconia fibers were immersed in a 0.03 mol / L dopamine hydrochloride solution and sonicated for 40 min. The pH of the system was adjusted to 8.0 using a 0.01 mol / L Tris buffer solution. The reaction was carried out at room temperature with stirring for 1-3 h. After the reaction was completed, the fibers were washed with water and dried in a vacuum drying oven at 70℃ to obtain the preliminary modified fibers. (2) The preliminarily modified fiber was immersed in an ethanol dispersion of europium nitrate at 3.0 g / L, stirred at 55°C for 1.5 h, then centrifuged, washed with water, and dried in an oven at 105°C for 2 h to obtain modified zirconia fiber.

[0088] The preparation method of the silicate adhesive includes the following specific steps: (1) Weigh 0.28 parts of dispersant (DISPERBYK-2013) and add it to 25 parts of solvent and stir for 30 min to obtain intermediate A; (2) Add 0.24 parts of the modified zirconium oxide fiber to intermediate A and stir for 60 min to obtain intermediate B; (3) Weigh 0.13 parts of surfactant (BYK-310) and add 5 parts of solvent and stir for 30 min to obtain intermediate C; (4) Add 21.4 parts of the weighed metal oxide (zirconia), 0.26 parts of the metal powder (Cu powder) and 0.26 parts of the modified glass powder to intermediate C and stir for 30 min to obtain intermediate D; (5) Weigh 27.5 parts of sodium silicate resin, add 17.79 parts of solvent and stir evenly, then add 2.1 parts of curing agent (sodium fluorosilicate) to obtain intermediate E; (6) Slowly add intermediate D to intermediate E and stir for 50 minutes until the mixture is evenly distributed to form slurry F; (7) Slowly add intermediate B to slurry F and stir for 30 minutes. After mixing evenly, add 0.3 parts of defoamer (BYKETOL-WA) to form slurry. (8) Place the slurry in a grinding instrument and grind it at a grinding rate of 1 r / min to obtain silicate adhesive; (9) Apply the silicate adhesive obtained in step (8) to the substrate and cure it at 204°C for 2 hours. After curing, cool it to room temperature in the oven.

[0089] Example 2 A silicate adhesive comprising the following components by weight: The composition comprises 28.3 parts potassium silicate resin, 1.9 parts curing agent (magnesium metaborate), 23.1 parts metal oxide (alumina), 0.31 parts metal powder (Al powder), 0.36 parts modified glass powder, 0.25 parts modified zirconia fiber, 0.15 parts surfactant (BYK-3456), 0.30 parts dispersant (DISPERBYK-190), and 0.31 parts defoamer (BYKETOL-WA), with the balance being 45.38 parts solvent. The solvent, by volume percentage, is composed of 30% anhydrous ethanol and 70% deionized water.

[0090] The preparation method of the silicate adhesive described in this embodiment is the same as that in embodiment 1, except that 15.38 parts of solvent are added in step (5).

[0091] Example 3 A silicate adhesive comprising the following components by weight: The composition comprises 29.8 parts of a mixture of sodium silicate resin and potassium silicate resin, 1.7 parts of a curing agent (sodium tripolyphosphate), 24.3 parts of a metal oxide (magnesium oxide), 0.45 parts of a metal powder (Fe powder), 0.15 parts of modified glass powder, 0.26 parts of modified zirconium oxide fiber, 0.17 parts of a surfactant (BYK-348), 0.31 parts of a dispersant (DISPERBYK-2013), and 0.33 parts of a defoamer (BYKETOL-WA), with the balance being 42.68 parts of solvent. The mass percentage of sodium silicate resin to potassium silicate resin is 1.9:1; the solvent, by volume percentage, is composed of 35% anhydrous ethanol and 65% deionized water.

[0092] The preparation method of the silicate adhesive described in this embodiment is the same as that in embodiment 1, except that 12.68 parts of solvent are added in step (5).

[0093] Comparative Example 1 Same as Example 1, except that no modified glass powder was added.

[0094] Comparative Example 2 Same as Example 1, except that the modified glass powder is replaced with an equal amount of untreated glass powder.

[0095] Comparative Example 3 Same as Example 1, except that the glass powder is modified with a single γ-glycidoxypropyltrimethoxysilane.

[0096] Comparative Example 4 Same as Example 1, except that glass powder is modified with a single vinyltriethoxysilane.

[0097] Comparative Example 5 Same as Example 1, except that no modified zirconium oxide fiber was added.

[0098] Comparative Example 6 Same as Example 1, except that the modified zirconia fibers are replaced with an equal amount of zirconia fibers that have not undergone any surface treatment.

[0099] Comparative Example 7 Same as Example 1, except that only step (1) polydopamine modification treatment is performed.

[0100] Comparative Example 8 Same as Example 1, except that only step (2) europium nitrate modification treatment is performed.

[0101] Test case (a) Test the properties of the silicate adhesives prepared in Examples 1-3. See Table 1 for details.

[0102] Table 1

[0103] As shown in Table 1, the silicate adhesive prepared by this invention is a grayish-white paste with a viscosity maintained between 5000 and 7000 (mPa·s) and a pH value between 11 and 13. After soaking in 30% hydrochloric acid solution and 30% NaOH solution for 24 hours, no blistering, cracking, or peeling occurred on the surface.

[0104] The tensile shear strength test results show that the silicate adhesive prepared by this invention has extremely high shear strength under standard atmospheric pressure at room temperature, remaining between (27.3~28.1) MPa. It can withstand greater tensile and shear forces, is less prone to delamination and cracking, has significantly improved load-bearing capacity, a long service life, reduces the failure rate of adhesive bonding, and enhances the safety and usability of structural connectors.

[0105] The experimental results of temperature resistance show that the silicate adhesive prepared by this invention does not exhibit cracking, peeling, or flaking on the surface under the test conditions, demonstrating good temperature resistance.

[0106] The results of the high and low temperature alternating cycle test show that the silicate adhesive prepared by this invention exhibits no cracking, peeling, or flaking on the surface after 50 cycles under the test conditions, demonstrating good resistance to thermal expansion and contraction fatigue and good reliability.

[0107] The water resistance test results show that the water absorption rate of the silicate adhesive prepared by this invention is less than 2%, indicating that the adhesive can avoid engineering quality and safety risks caused by hydrolysis, softening, delamination, and detachment. It also demonstrates that the adhesive of this invention has complete curing, a dense structure, and strong water molecule penetration barrier, which is beneficial for maintaining the interfacial bonding between the adhesive layer and the substrate.

[0108] Therefore, silicate adhesives have high bonding strength and excellent bonding performance with matrix materials, making them ideal candidate materials in the field of inorganic adhesives.

[0109] 2) Test the performance of the silicate adhesives prepared in Comparative Examples 1-8. The specific test conditions are the same as those in Experiment 1, as detailed in Table 2.

[0110] Table 2

[0111] As shown in Table 2, the silicate adhesives prepared by Comparative Examples 1-8 of the present invention have low overall performance. Their maximum bonding strength is only 32.9 MPa and their maximum tensile shear strength is 9.3 MPa, which are far less than the performance of the adhesives described in Examples 1-3. Their water absorption rate is ≥3.5%, which is higher than that of Examples 1-3 of the present invention.

[0112] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A silicate adhesive, characterized in that, By weight, it comprises the following components: The composition includes 26-30 parts silicate resin, 1.7-2.2 parts curing agent, 20-25 parts metal oxide, 0.25-0.55 parts metal powder, 0.15-0.36 parts modified glass powder, 0.23-0.27 parts modified zirconia fiber, 0.13-0.17 parts surfactant, 0.28-0.32 parts dispersant, 0.29-0.33 parts defoamer, and the balance being solvent.

2. The silicate adhesive according to claim 1, characterized in that, The method for preparing the modified glass powder includes the following steps: γ-glycidoxypropyltrimethoxysilane and vinyltriethoxysilane were mixed in a certain proportion and then added to a certain amount of anhydrous ethanol. The mixture was stirred until homogeneous to obtain a mixed liquid with a mass fraction of 1.0-5.5%. Glass powder was added to the mixed liquid and the reaction was carried out. After the reaction was completed, the mixture was filtered and dried to obtain modified glass powder.

3. The silicate adhesive according to claim 2, characterized in that, The mass ratio of γ-glycidoxypropyltrimethoxysilane to vinyltriethoxysilane is 1:3-5; the amount of the mixture of γ-glycidoxypropyltrimethoxysilane and vinyltriethoxysilane added accounts for 1.2%-3.7% of the total mass of the glass powder; the D of the glass powder 50 The size is (180-300) μm; the reaction temperature is (50-80) ℃, and the reaction time is 30 min-180 min.

4. The silicate adhesive according to claim 1, characterized in that, The preparation method of the modified zirconia fiber includes the following steps: (1) Immerse the zirconia fiber in a dopamine hydrochloride solution and sonicate for (20-50) min. Adjust the pH of the system to the range of 7.5-8.

5. Stir and react at room temperature. After the reaction is completed, wash with water and dry to obtain the preliminary modified fiber. (2) The preliminarily modified fiber was soaked in an ethanol dispersion of europium nitrate (2.5-4.0) g / L and stirred at 55°C for (1-3) h. Then it was centrifuged, washed with water and dried to obtain modified zirconia fiber.

5. The silicate adhesive according to claim 4, characterized in that, The concentration of the dopamine hydrochloride solution in step (1) is 0.02 mol / L-0.05 mol / L; the reaction time is 1-3 h; and the drying temperature is 60-80℃.

6. The silicate adhesive according to claim 1, characterized in that, The silicate resin is any one or two of sodium silicate resin and potassium silicate resin; the curing agent is any one of fluorosilicate, metaborate, tripolyphosphate, and methyl palmitate; the metal oxide is any one of silicon dioxide, zirconium dioxide, aluminum oxide, cobalt oxide, iron oxide, and chromium oxide; and the metal powder is any one of Cu powder, Al powder, and Fe powder.

7. The silicate adhesive according to claim 1, characterized in that, The surfactant is a polyether-modified siloxane; the dispersant is a styrene-maleic anhydride copolymer; the defoamer is a mixture of a high-boiling-point solvent and a defoaming substance; and the solvent is a mixed solution of anhydrous ethanol and water.

8. The method for preparing the silicate adhesive according to any one of claims 1-7, characterized in that, Includes the following steps: (1) Weigh the dispersant and add an appropriate amount of solvent and stir to obtain intermediate A; (2) The weighed modified zirconium oxide fiber was added to intermediate A and stirred to obtain intermediate B; (3) Weigh the surfactant, add an appropriate amount of solvent and stir to obtain intermediate C; (4) Add the weighed metal oxide, metal powder and modified glass powder to intermediate C and stir to obtain intermediate D; (5) Weigh the silicate resin, add an appropriate amount of solvent and stir evenly, then add the curing agent to obtain intermediate E; (6) Slowly add intermediate D to intermediate E and stir until the mixture is evenly distributed to form slurry F; (7) Slowly add intermediate B to slurry F and stir. After mixing evenly, add defoamer to form slurry G; (8) Grind the slurry G in a grinding instrument to obtain silicate adhesive.

9. The method for preparing the silicate adhesive according to claim 8, characterized in that, In steps (1) to (7), the stirring time is 30 to 60 minutes; in step (8), the grinding rate is 1 to 3 r / min.

10. A method of using the silicate adhesive according to any one of claims 1-7, comprising the following steps: The silicate adhesive is applied to the substrate and then heated to cure.

Citation Information

Patent Citations

  • Modified silicate inorganic adhesive

    CN103059748A

  • Silicate inorganic adhesive and preparation method thereof

    CN106519993A

  • Silicate inorganic adhesive as well as preparation method and use method thereof

    CN113683966A

  • High-temperature-resistant inorganic adhesive and preparation method thereof

    CN115353809A

  • Impact-resistant seawall repairing cementing material and preparation method thereof

    CN117327452A